INTEGRATED MECHANISM OF REHABILITATION OF CHILDREN WITH CHILDHOOD CEREBRAL PALSY IN CLINICAL AND POST-CLINICAL CONDITIONS (Academia Science Repository, 2023)
Development of affordable physical exercises that increase the effectiveness of therapy in patients with cerebral palsy. Examination and rehabilitation of 38 patients with cerebral palsy of various forms was carried out. In the main group, classes at home were added to the complex treatment. The effectiveness of therapy in categories: communication, movement, self-service, play activity was greater in the group where physical therapy was used at home. The need for further development of methods for the rehabilitation of children with disabilities is shown.